Kewajiban Alimentasi Anak Kepada Orang Tua yang Berada Di Panti Sosial Merupakan Hubungan Hukum Akibat Perkawinan Dan Hubungan Darah - Veronica Komalawati; Sridewi Anggraeni; Alma Ardelia Ma'arif (LPPM Universitas Jambi, 2021)
A legal marriage paves the road to start a family in accordance with the law, which creates various legal relationships in the area of family law. One of the legal relationships that arise between a child and his/her parents is the obligation of reciprocal alimentation. The legal obligation of alimony refers to the act of providing someone with financial support based on the capability of the person providing alimony. When a legally married couple decides to have a child, the parents have control over that child which creates the legal obligation for the parents to raise and educate the child as best they could until that child reaches adulthood. When that child reaches adulthood, he/she must take care of the parents in need of assistance, in accordance with the child’s capability. However, in reality adults often neglect their parents, abandoning them when they need assistance by handing over responsibility to a social institution. Cases where the child neglects their elderly parents often occur since the child does not have a familial connection with his/her parents because the parents were absent during the child’s upbringing. The obligation of the child to provide elderly parents with alimony constitutes a legal relationship that cannot be broken according to family law due to the existence of a legal marriage and blood relations. Even when the parents have been placed at a social institution for whatever reason, the child who has reached adulthood is obligated to provide the parents alimony and show respect.